Nucleotide sequence encoding the flavoprotein and iron-sulfur protein subunits of the Bacillus subtilis PY79 succinate dehydrogenase complex. - Phillips, M K (1987)
The nucleotide sequence of a 2.7-kilobase segment of DNA containing the sdhA and sdhB genes encoding the flavoprotein (Fp, sdhA) and iron-sulfur protein (Ip, sdhB) subunits of the succinate dehydrogenase of Bacillus subtilis was determined. This sequence extends the previously reported sequence encoding the cytochrome b558 subunit (sdhC) and completes the sequence of the sdh operon, sdhCAB. The predicted molecular weights for the Fp and Ip subunits, 65,186 (585 amino acids) and 28,285 (252 amino acids), agreed with the values determined independently for the labeled Fp and Ip antigens, although it appeared that the B. subtilis Fp was not functional after expression of the sdhA gene in Escherichia coli. Both subunits closely resembled the corresponding Fp and Ip subunits of the succinate dehydrogenase (SDH) and fumarate reductase of E. coli in size, composition, and amino acid sequence. The sequence homologies further indicated that the B. subtilis SDH subunits are equally related to the SDH and fumarate reductase subunits of E. coli but are less closely related than are the corresponding pairs of E. coli subunits. The regions of highest sequence conservation were identifiable as the catalytically significant flavin adenine dinucleotide-binding sites and cysteine clusters of the iron-sulfur centers.